2020
DOI: 10.30897/ijegeo.627856
|View full text |Cite
|
Sign up to set email alerts
|

Ecology of Benthic Foraminifera of the Eastern Aegean Sea Coasts

Abstract: The aim of this study was to determine the distribution of benthic foraminifera in some field of the Turkish Aegean coasts have been investigated and the effects of ecological changes observed on these fauna in 2009-2014 period. Sediment samples from Alibey and Maden Islands (Balıkesir), Kuşadası (Aydın), Çeşme Ilıca Bay (Izmir) and northwestern coast of Karaburun Peninsula (Izmir) have been analysed. Similarities, as well as dissimilarities were observed between the assemblages from different locations. The R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…This species is a prolific carbonate producer (Hallock, 1981;Langer et al, 1997;Langer, 2008) and displays extreme forms of ecosystem invasibility (Langer et al, 2012;Mouanga & Langer, 2014;Langer & Mouanga, 2016). This includes mass occurrences, hyperabundances and the appearance in mono-cultures, with capabilities to reduce native diversity and species richness (Mouanga & Langer, 2014), to transform the composition, grain size and chemistry of sediments from predominantly siliceous to carbonate deposits (Hyams et al, 2002;Samir et al, 2003;Gruber, 2007;Yokeş & Meriç, 2009;Abu Tair & Langer, 2010;Langer et al, 2012;Weinmann et al, 2013;Caruso & Cosentino, 2014;Mouanga & Langer, 2014;Guastella et al, 2019;Meriç et al, 2020), and to trigger changes in ecosystem functioning (Langer et al, 2012). Triantaphyllou et al (2005), Koukousioura et al (2011), and Dimiza et al (2016b) have suggested that their presence and numerical abundance may be used as proxy to assess the degree of environmental disturbance.…”
Section: Discussionmentioning
confidence: 99%
“…This species is a prolific carbonate producer (Hallock, 1981;Langer et al, 1997;Langer, 2008) and displays extreme forms of ecosystem invasibility (Langer et al, 2012;Mouanga & Langer, 2014;Langer & Mouanga, 2016). This includes mass occurrences, hyperabundances and the appearance in mono-cultures, with capabilities to reduce native diversity and species richness (Mouanga & Langer, 2014), to transform the composition, grain size and chemistry of sediments from predominantly siliceous to carbonate deposits (Hyams et al, 2002;Samir et al, 2003;Gruber, 2007;Yokeş & Meriç, 2009;Abu Tair & Langer, 2010;Langer et al, 2012;Weinmann et al, 2013;Caruso & Cosentino, 2014;Mouanga & Langer, 2014;Guastella et al, 2019;Meriç et al, 2020), and to trigger changes in ecosystem functioning (Langer et al, 2012). Triantaphyllou et al (2005), Koukousioura et al (2011), and Dimiza et al (2016b) have suggested that their presence and numerical abundance may be used as proxy to assess the degree of environmental disturbance.…”
Section: Discussionmentioning
confidence: 99%